Korupsi APBD: Ekses Negatif Otonomi Daerah (Pentingnya Kebijakan Transparansi Pengelolaan Anggaran dalam APBD) - Yana Karyana (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2004)
This article tries to analyses the negative aspects of the impact of the implementation of decentralisation policy in Indonesia. The author argues that the ill-preparedness of the local governments to carryout the policy such as lack of qualified personnel and lack of control in allocating and disbursing the budget are among other factors which cause. the incident of the so-called korupsi terstruktur (structured corruption)